Analisis Penggunaan Helicopter Stand dalam Menunjang Keamanan dan Keselamatan Penerbangan di Bandar Udara Tjilik Riwut Palangka Raya - Yoga Abian Pratama; Dhiani Dyahjatmayanti (Pusat Riset dan Inovasi Nasional, 2025)
Tjilik Riwut Palangka Raya Airport is one of the main gateways in Central Kalimantan province. In 2023, the airport will serve around 40,000 passengers, indicating an increase in aviation activity that requires high efficiency in facility management. Helicopters at Tjilik Riwut Airport have an important role in various operations, including medical evacuation, goods delivery and government missions. Currently, helicopters only land in regular commercial aircraft parking areas, which are not specifically designed for helicopter needs. This can cause a buildup of activity, disrupting flight schedules. This research aims to analyze the needs and benefits of building a Helicopter Stand at Tjilik Riwut Airport, as well as assessing its impact on the smooth running of flights. This research uses qualitative methods and the types of data used are primary data and secondary data. The data collection techniques used in this research are observation, interviews and documentation. By using analytical techniques in the form of data reduction, data presentation and conclusions. Testing the validity of the data used in this research is technical triangulation and source triangulation. The results of this research show that the helicopter stand facilities at Tjilik Riwut Airport are currently not fully adequate, it is necessary to reorganize the area to ensure clearer separation between helicopters and commercial aircraft in order to reduce the potential for accidents and avoid the potential for overlapping with other aircraft in the parking stand area.